(untitled) (American Journal of Islam and Society, 1991)
Jamal al Din ’Atiyah, academic advisor to the IIIT-Cairo office, recently presided over the office’s monthly public lecture entitled "Pluralism in Islam." Among the speakers were Jamal al Din ’A, Mul)ammad ’lmarah, Mul)ammad al GhazzaH, Mul)ammad Kamal Imam, Sa’id ·Ashur, and Mubammad Salim al ’Awa. In his presentation, ’Atiyah emphasized that the concept of pluralism is not limited to politics, as it is actually the source, if we compare it to the true unity or oneness which is an attribute of Allah alone. This being the case, everything else is subject to pluralism. ’Atiyah, expounding upon the Qur’anic verses which mention pluralism in creation, said that they were many and that they illustrate the Creator’s greatness as well as His creation’s uniqueness. The signs of plurality in nature turn humanity’s attention to the purpose for which plurality was created: the manifestation and uniqueness of the One Creator in the variety and difference of creation. There is also the concept that a pluralistic creation seeks to get the sexes as well as various peoples and tribes to know each other so that they can produce a civilization and progress. Requiring such interaction lead to cooperation, and this difference in abilities-as in the case of the sexesleads to completion. If we imagine lhat there is only one type of person, people will not get to know each other, and each one of u will be a copy of the others. ’Atiyah explained that the concept of pluralism was clear to people at the international level both before and after Islam. He said that no single nation has ever ruled over or controlled the entire world. In short, pluralism leads to balance and competition among nations, thus preserving the order of creation. As for pluralism within the ummah, he said that the ummah is united and that this has been stated in many texts. The ummah established its unity in the early years of Islam with the founding of the Islamic state in Madinah. As for political pluralism or political groupings within the Islamic ummah, ’Atiyah said that the ummah must encourage those political activities which will allow the development of several parties. These parties may be divided into two types: those which work inside and those which work outside the framework of general Islamic concepts. This idea is not universally accepted however, for some say that only the first type of party should be allowed ...